Organizational citizenship behaviours, managerial ties and organizational culture : impact on open innovation / Mohmmad Muzamil Naqshbandi - Naqshbandi, Mohmmad Muzamil (2013)
in the Open Innovation paradigm offers great benefits to firms and supplants their reliance on expensive internal R&D. Many firms have succeeded in the Open Innovation paradigm but failures have also been reported. Being a new area of research, not much is known about the factors affecting Open Innovation. In view of this, the current research was conducted with the aim to study the effects of Organizational Citizenship Behaviours, Organizational Culture and Managerial Ties (predictor variables) on Open Innovation (criterion variable) and to study the moderating role of Regimes of Appropriability on these relationships. Cross-sectional data were collected using the survey method from 339 middle and top managers working in manufacturing firms in the four high-tech industries in Malaysia. A two-stage sampling procedure involving stratified sampling and convenience sampling techniques was used. Hierarchical multiple regression was employed to test the hypothesized relationships. The results reveal that Organizational Citizenship Behaviors predicts Open Innovation positively and significantly. In addition, Highly Integrative Culture was found to relate positively to In-bound Open Innovation while Hierarchy Culture related negatively. No evidence of a significant relationship between Organizational Culture and Out-bound Open Innovation was found. Managerial Ties with government officials and with universities and/or other research centers were found to facilitate In-bound Open Innovation while Managerial Ties with managers at other firms did not significantly affect In-bound Open Innovation. Besides, no statistically significant relationship was found between Managerial Ties and Out-bound Open Innovation. In addition, Regimes of Appropriability was not found to moderate strongly the relationships between the predictor and the outcome variables. The study makes many theoretical and managerial contributions which, along with the limitations of this research and future research directions, are highlighted in this thesis.